2007
DOI: 10.1021/om0701524
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the Generation of Ketenimine−M(CO)n Complexes (M = Cr, W, Fe) from Fischer Carbenes and Isocyanides

Abstract: The mechanism of the thermal formation of ketenimine complexes through the reaction of group 6 (chromium and tungsten) and 8 (iron) Fischer carbenes and isocyanides has been studied computationally within the density functional theory framework. The computational data have been compared to the reported experimental results. It is found that the insertion of the N⋮C bond of the isocyanide into the MC bond of the Fischer carbene complexes, which leads to N-metalated-ketenimine complexes, occurs via metallacyclo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 50 publications
1
18
0
Order By: Relevance
“…As shown in Scheme 60, the reaction of Fisher carbene 171 with isocyanide has been developed for the synthesis of ketenes 172. 35 This transformation was mechanistically similar to 1,2-insertion of triple N-C bond of isocyanide into the double MQC bond of carbene.…”
Section: Isocyanide Insertion Into Metal Carbene Compoundsmentioning
confidence: 91%
“…As shown in Scheme 60, the reaction of Fisher carbene 171 with isocyanide has been developed for the synthesis of ketenes 172. 35 This transformation was mechanistically similar to 1,2-insertion of triple N-C bond of isocyanide into the double MQC bond of carbene.…”
Section: Isocyanide Insertion Into Metal Carbene Compoundsmentioning
confidence: 91%
“…Theg eneral mechanism of the insertion of isocyanides via carbene transfer into the TM= Cb ond of Fischer carbenes 147 was extensively investigated in silico by Sierra and co-workers. [69] They showed that am etallacyclopropanimine intermediate 150 is more likely than the previously considered zwitterionic species 149 (Scheme 38). 1,2-Metallotropic rearrangement of 150 then affords N-metalated ketenimine 148.…”
Section: Insertion Of Isocyanides Into Metal Carbene Complexesmentioning
confidence: 98%
“…In particular, the reactions of isocyanides with metal carbene complexes are known to form ketenimine complexes, which, in turn, are valuable intermediates and powerful synthetic tools [76]. The mechanism of the reaction of Fischer-type carbenes with methylisocyanide was studied theoretically by DFT method [77,78]. The reaction is believed to proceed via metallacyclopropanimine species which are generated by nucleophilic attack of the isocyanide carbon atom on the electrophilic carbene carbon (Scheme 6).…”
Section: Addition Of Isocyanides To Coordinated Ligandsmentioning
confidence: 99%